A new predictor of U.S. real economic activity: The S&P 500 option implied risk aversion - Renato Faccini; Eirini Konstantinidi; George Skiadopoulos; Sylvia Sarantopoulou-Chiourea (Queen Mary University of London, School of Economics and Finance, 2018)
We propose a new predictor of U.S. real economic activity (REA), namely the representative investor's implied relative risk aversion (IRRA) extracted from S&P 500 option prices. IRRA is forward-looking and hence, it is expected to be related to future economic conditions. We document that U.S. IRRA predicts U.S. REA both in-and out-of-sample once we control for well-known REA predictors and take into account their persistence. An increase (decrease) in IRRA predicts a decrease (increase) in REA. We extend the empirical analysis by extracting IRRA from the South Korea, UK, Japanese and German index option markets. We find that South Korea IRRA predicts the South Korea REA both in-and out-of-sample, as expected given the high liquidity of its index option market. We show that a parsimonious yet flexible production economy model calibrated to the U.S. economy can explain the documented negative relation between risk aversion and future economic growth.
Keywords: E44; G13; G17; 330; Option prices; Risk aversion; Risk-neutral moments; Real Economic Activity; Production economy model